Change of Nutritional Status Assessed Using Subjective Global Assessment Is Associated With All-Cause Mortality in Incident Dialysis Patients. Issue 7 (February 2016) - Kwon, Young Eun; Kee, Youn Kyung; Yoon, Chang-Yun; Han, In Mee; Han, Seung Gyu; Park, Kyoung Sook; Lee, Mi Jung; Park, Jung Tak; Han, Seung H.; Yoo, Tae-Hyun; Kim, Yong-Lim; Kim, Yon Su; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Subjective global assessment (SGA) is associated with mortality in end-stage renal disease (ESRD) patients. However, little is known whether improvement or deterioration of nutritional status after dialysis initiation influences the clinical outcome. We aimed to elucidate the association between changes in nutritional status determined by SGA during the first year of dialysis and all-cause mortality in incident ESRD patients. This was a multicenter, prospective cohort study. Incident dialysis patients with available SGA data at both baseline and 12 months after dialysis commencement (n = 914) were analyzed. Nutritional status was defined as well nourished (WN, SGA A) or malnourished (MN, SGA B or C). The patients were divided into 4 groups according to the change in nutritional status between baseline and 12 months after dialysis commencement: group 1, WN to WN; group 2, MN to WN; group 3, WN to MN; and group 4, MN to MN. Cox proportional hazard analysis was performed to clarify the association between changes in nutritional status and mortality. Being in the MN group at 12 months after dialysis initiation, but not at baseline, was a significant risk factor for mortality. There was a significant difference in the 3-year survival rates among the groups (group 1, 92.2%; group 2, 86.0%; group 3, 78.2%; and group 4, 63.5%; log-rank test, P < 0.001). Multivariate Cox regression analysis revealed that the mortality risk was significantly higher in group 3 than in group 1 (hazard ratio [HR] 2.77, 95% confidence interval [CI] 1.27–6.03, P = 0.01) whereas the mortality risk was significantly lower in group 2 compared with group 4 (HR 0.35, 95% CI 0.17–0.71, P < 0.01) even after adjustment for confounding factors. Moreover, mortality risk of group 3 was significantly higher than in group 2 (HR 2.89, 95% CI 1.22–6.81, P = 0.02); there was no significant difference between groups 1 and 2. The changes in nutritional status assessed by SGA during the first year of dialysis were associated with all-cause mortality in incident ESRD patients.